The Law-Medicine Relation: A Philosophical Exploration
XXX, 293 p.
Keywords: This volume is a contribution to the continuing interaction between law and medicine. Problems arising from this interaction have been addressed, in part, by previous volumes in this series. In fact, one such problem constitutes the central focus of Volume 5, Mental Illness: Law and Public Policy [1]. The present volume joins other volumes in this series in offering an exploration and critical analysis of concepts and values underlying health care. In this volume, however, we look as well at some of the general questions occasioned by the law's relation with medicine. We do so out of a conviction that medi cine and the law must be understood as the human creations they are, reflect ing important, wide-ranging, but often unaddressed aspects of the nature of the human condition. It is only by such philosophical analysis of the nature of the conceptual foundations of the health care professions and of the legal profession that we will be able to judge whether these professions do indeed serve our best interests. Such philosophical explorations are required for the public policy decisions that will be pressed upon us through the increasing complexity of health care and of the law's response to new and changing circumstances. As a consequence, this volume attends as much to issues in public policy as in the law. The law is, after all, the creature of human deci sions concerning prudent public policy and basic human rights and goods.